2003
DOI: 10.1063/1.1555691
|View full text |Cite
|
Sign up to set email alerts
|

Formation of crystalline Si nanodots in SiO2 films by electron irradiation

Abstract: Amorphous SiO2 transforms into crystalline Si by 200 kV electron irradiation at ambient temperature. The transformation of amorphous SiO2 to crystalline Si takes place in two steps; the first step involves transformation of amorphous SiO2 into amorphous Si, while the second step is the crystallization of amorphous Si. Valence electron ionization is determined as the key factor for the transformation from SiO2 to amorphous Si; beam heating and knock-on displacement are responsible for the transformation from am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 11 publications
1
55
2
Order By: Relevance
“…Therefore, we expect the sticking probability of Si 5 H 12 to be much larger than the one of F e(CO) 5 and, thus, the coverage probability of neopentasilane to be much higher than the one of iron pentacarbonyl. This picture is maintained until the flux of F e(CO) 5 Electron irradiation has been used to induce phase transformations in bulk and low dimensional systems [27,28], and to tune the physical properties of graphene and carbon nanotubes [29]. In a series of recent papers we have started to investigate the effects of electron beam irradiation on the microstructure of FEBID samples [19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we expect the sticking probability of Si 5 H 12 to be much larger than the one of F e(CO) 5 and, thus, the coverage probability of neopentasilane to be much higher than the one of iron pentacarbonyl. This picture is maintained until the flux of F e(CO) 5 Electron irradiation has been used to induce phase transformations in bulk and low dimensional systems [27,28], and to tune the physical properties of graphene and carbon nanotubes [29]. In a series of recent papers we have started to investigate the effects of electron beam irradiation on the microstructure of FEBID samples [19].…”
Section: Discussionmentioning
confidence: 99%
“…Crystallization of the glassy phase is induced not only by heat treatments but by other methods such as electron irradiation, [9][10][11] ion irradiation, 12) electropulsing 13) and high pressure. 14) It has been demonstrated that electron irradiation can induce nanocrystallization in metallic glasses in which nanoscale structures cannot easily be realized by heat treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Heating could be ruled out as the main cause of crystallization as in-situ annealed (400-F o r P e e r R e v i e w 600 °C) samples retained in their amorphous state. This is a higher temperature than expected from the electron beam heating of the samples [20][21][22] . These findings highlight the need for great care in imaging these kinds of materials for a correct structure characterization.…”
Section: Introductionmentioning
confidence: 63%
“…For Zr-Si-C, in-situ annealing in X-ray diffractometer in a vacuum furnace (base pressure 5*10 -5 Pa) showed thermally induced crystallization between 500-700 °C [13] . However, the increase of temperature by the electron beam is not expected to be that high [20][21][22] . Thus, we drew the conclusion [20] that atomic displacement is the main cause of crystallization during electron microscopy studies.…”
Section: Resultsmentioning
confidence: 99%